Pengaruh Teknologi Digital terhadap Pengembangan Usaha Mikro, Kecil, dan Menengah di Buahbatu - Muhammmad Rizqi Hartono; Deri Apriadi (Pusat Riset dan Inovasi Nasional, 2025)
One of the main strategies used by the government to empower communities and accelerate the economic growth of a country is the existence of Micro, Small, and Medium Enterprises (MSMEs). Digital technology, in addition to other technical advances, is currently having a major impact on society by making it easier for businesses of all sizes to operate and gain recognition across borders. The main objective of this study is to find out how the use of advanced technology can boost the income of MSMEs in Buahbatu. This system uses the SPSS 26 variation program to integrate various iterative examination processes. Both additional information and information used are equally significant. The scientists themselves collect research data through a selection process using observational polls with a questionnaire list. The results of the study show that the application of digital technology has a positive and significant impact on the growth of income of Micro, Small, and Medium Enterprises (MSMEs) in Buahbatu Regency. This study shows that the use of digital technology can increase marketing space, income, and output.